2011
DOI: 10.1038/hr.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

Circulating progenitor cells are increased in newly diagnosed untreated hypertensive patients with arterial stiffening but normal carotid intima-media thickness

Abstract: Circulating progenitor cells (CPCs), including endothelial progenitor cells (EPCs), have a key role in endothelium repair. Cellular NADPH oxidase (Nox) enzymes, including Nox-containing gp91phox, represent a source of reactive oxygen species (ROS); ROS trigger protective signals but may also have detrimental effects. Cellular defenses against ROS include the enzymes manganese superoxide dismutase (MnSOD), catalase (CAT) and glutathione peroxidase type-1 (GPx-1). We investigated the relationships of CPCs with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…During this process, they are exposed to shear stress generated by interstitial fluid flow and blood flow, and it has been reported that when cultured EPCs undergo shear stress in a flow‐loading device, their differentiation into mature endothelial cells accelerates significantly (Yamamoto et al, 2003). In recent evidence, other researchers showed that the levels of a different phenotype of EPCs were increased in newly diagnosed untreated patients with hypertension with arterial stiffening but normal carotid IMT; the EPC numbers correlated with gp91phox (a source of oxidative stress), a reactive oxygen species and fibrinogen, suggesting that the EPC number may be increased in early phases of atherosclerosis before the development of wall thickening to maintain an adequate number of EPCs in peripheral blood (Mandraffino et al, 2011). Based on this model, further studies will clarify if correlations exist among oxidative stress, cavernous intimal thickness, and EPC numbers in patients with AED or if this alteration (increased IMT) occurs first for different calibers of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, they are exposed to shear stress generated by interstitial fluid flow and blood flow, and it has been reported that when cultured EPCs undergo shear stress in a flow‐loading device, their differentiation into mature endothelial cells accelerates significantly (Yamamoto et al, 2003). In recent evidence, other researchers showed that the levels of a different phenotype of EPCs were increased in newly diagnosed untreated patients with hypertension with arterial stiffening but normal carotid IMT; the EPC numbers correlated with gp91phox (a source of oxidative stress), a reactive oxygen species and fibrinogen, suggesting that the EPC number may be increased in early phases of atherosclerosis before the development of wall thickening to maintain an adequate number of EPCs in peripheral blood (Mandraffino et al, 2011). Based on this model, further studies will clarify if correlations exist among oxidative stress, cavernous intimal thickness, and EPC numbers in patients with AED or if this alteration (increased IMT) occurs first for different calibers of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we identified and counted circulating CD34+ cells in peripheral blood. The cells were analyzed for the expression of surface antigens with direct multi-color analysis using fluorescein isothiocyanate (FITC)-conjugated, and phycoerythrin (PE)-conjugated monoclonal antibodies (mAbs) by flow cytometry analysis, as reported elsewhere [ 33 ]. Staining and analysis were performed using the International Society of Hematotherapy and Graft Engineering (ISHAGE) sequential strategy [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the very early stage of hypertension a significant increase in circulating progenitor cells is associated with reactive oxygen species and oxidative stress [73] . Vasa et al [19] , after studying patients with CAD concluded that the migratory capacity of EPCs was reduced in those patients with hypertension, although their total number did not change significantly.…”
Section: Epcs and Arterial Hypertensionmentioning
confidence: 99%